Multistakeholder Collaborative Effort to Enhance Long-Term Follow-Up in the Abdominal Core Health Quality Collaborative - Benjamin K. Poulose, MD, MPH, FACS; Harriet Schwartzman, BA; Li-Ching Huang, PhD; Scott Chouinard, PhD; Donald Coelho, BA; David Macarios, MBA, MSc; Sundeep Master, MBA; Michael J. Rosen, MD, FACS (Annals of Surgery Open, 2021)
Objective:. To determine the effectiveness of a clinical call center in performing focused long-term patient reported outcome (PRO)-based follow-up for ventral hernia patients in routine practice. Background:. Long-term follow-up remains the mainstay of assessing quality of care in hernia management. Achieving acceptable rates of long-term follow-up outside of clinical trials in the routine care of patients has been very difficult to achieve. Methods:. A prospective quality improvement intervention using a clinical call center in 1000 random patients eligible for long-term (1 year or greater) follow-up after ventral hernia repair in the Abdominal Core Health Quality Collaborative was performed. The primary outcome measure was the proportion of patients with successfully completed PRO-based long-term follow-up. Results:. Between 2013 and 2017, the baseline long-term follow-up PRO completion rate was 2167/13,950 (15.5%). For the Focus on Follow-Up initiative, 890 patients were eligible for contact; a completion rate of 450/890 (50.6%, P < 0.001) was achieved. Conclusions:. Clinical call center-based patient contact can greatly facilitate the completion of PROs utilized for long-term follow-up in ventral hernia repair. This has important implications for quality improvement programs and postmarket device surveillance.